Thermal activation of persulfates for wastewater depollution on pilot scale solar equipment. (15th July 2020) - Telegang Chekem, C.; Chiron, S.; Mancaux, J.M.; Plantard, G.; Goetz, V.
Graphical abstract: Highlight: Efficiency of thermal induced activation of persulfate in removing micropollutants in WW . Up to 95% abatement with 200 µM of persulfate and 65 °C on a solar pilot equipment. Smart heat management system to tackle solar energy intermittency. Abstract: Thermal activation of new oxidant chemicals like Persulfate (PS) has recently gained attention in driving advanced oxidation processes (AOP) for a number of applications. On the other hand, addressing energy demand with carbon free and sustainable energy solutions represents an asset for new technologies in the modern society. This paper then investigates on the removal of pharmaceuticals residues in wastewater (WW), conducted with PS advanced oxidation reactions on a solar thermal pilot equipment. Indoor preliminary investigations on small scale laboratory experimentations show how increasing temperature has a direct positive impact on pollutants degradations rate ( kapp value ranging from 0.4·10 −3 s −1 at ambient to 10.4·10 −3 s −1 at 75 °C). However, after an experimental screening methodology, 65 °C and 200 µM appear as the appropriate target temperature and PS oxidant dosage to cope with both activation of PS oxidant and degradation of ten target micropollutants typically found in WW stream. Outdoor experimentations on the solar pilot equipment were conducted according to a batch running mode at a treatment capacity scale of a cubic meter. 95% pollutant removal rate is achieved within 2 h once the temperature has raised up to the target value (65 °C) in the bulk treated WW effluent. Series of treatment cycles under the natural day/night period demonstrate the reproducibility of the performance. As an early step result of the process optimization approach, heat recovery demonstration on the pilot equipment improves significantly the energetic balance over the now innovative thermal solar water treatment.